Interstate dialogue of Kazakhstan and China at the present stage: realities and prospects - Batpenova, Z. S.; Suleimenova, M. M. (Journal of Oriental Studies, 2016)
The article is dealing with analysis of approaches of the Kazakhstan and Chinese parties to the bilateral interstate relations, value of political dialogue of two countries in ensuring mutually beneficial cooperation in Central Asianregion at the present stage. Also the main directions of further development of interstate dialogue of China and Kazakhstan come to light.